Age, Sex, and Profession Difference Among Health Care Workers With Burnout and Metabolic Syndrome in Taiwan Tertiary Hospital—A Cross-Section Study - Tsai, Huel-Ju; Tsou, Meng-Ting (Frontiers in Medicine, 2022)
Background: This cross-sectional study aimed to analyze the association between burnout, work-related factors and metabolic syndrome (MetS) among various health-care workers (HCWs) at a tertiary hospital in Taiwan. Methods: Relevant demographic data were obtained through written questionnaires. Information about psychosocial and work conditions, including assigned department, working hours, shifts, and sleep condition, was obtained. Burnout was evaluated according to the Chinese version of Maslach Burnout Inventory–Health Services Survey. MetS was analyzed according to the criteria of the National Cholesterol Education Program of Taiwan–Treatment Panel for Adults III. Results: A total of 1,055 non-doctor/nurse and 2,078 doctor/nurse staff with a median age of 45.2 and 36.1 years participated in this study. The incidence of burnout was nearly 6.42% and 6.68% and that of MetS was 31.4% and 13.5% in non-doctor/nurse and doctor/nurse staff, respectively. The results showed that burnout induced a higher Odds ratio (OR) of MetS in the doctor/nurse group (OR = 1.96, p = 0.01). Other factors, such as night shift and seniority (>10 years), led to a higher OR of MetS, but a decreased risk was observed based on seniority (2–4 years). Further, young female participants and young doctors/nurses with burnout had a higher OR of MetS compare to other groups (OR = 2.43 and 2.32, p < 0.05). Conclusion: The study results suggested positive relationship between burnout and MetS in young female staffs and young doctors/nurses. For doctor/nurse staff with higher seniority or more night shifts, strategies are needed to prevent burnout and MetS.